In vitro Neuroprotective and Antioxidant Studies on Extract of Woodfordia fruticosa Flowers and its Phytochemical Analysis - M.C, Babitha; V, Gomathi; C, Uma Maheswara Reddy; M, Kumar; B.S, Venkateswarlu (Asian Journal of Biological and Life Sciences)
Aim: Medical illnesses known as Neurodegenerative Diseases (NDDs) have generated considerable attention in the science-based community. The in vitro approach for determining the antioxidant potentials of W. fruticosa flowers and their neuroprotective effects. Materials and Methods: Woodfordia fruticosa flower extract samples that underwent GC-MS analysis. DPPH and ABTS Radical Scavenging assays were performed. The neuroprotective potential of the selected extract was assessed using IMR-32 by MTT assay. Results: Twenty-one compounds were found in the methanolic leaf extract of Woodfordia fruticosa, according to the GC-MS analysis. Using the DPPH and ABTS assays, in vitro antioxidant activity was assessed. The standard and test samples produced various concentrations (12.5, 25, 50, 100, and 200 g/mL). Percentage suppression of the anti-oxidant action is shown. Ten distinct acetone extract compounds and nine different ethanol extraction components were found. Both preparations are more effective in scavenging free radicals as their concentration increases. Conclusion: The current research demonstrates W. fruticosa’s ability to protect neurons from Lipopolysaccharide-induced neurotoxicity in neuronal cells. Maximum cytotoxic effect was found in the MTT solubilization found better at high-end concentrations than at Lower concentrations among both extracts.
Keywords: Anti proliferative; Antioxidant; Ayurvedic; Cytotoxic; Furfural; Hexadecanoic acid